Utilizing Puzzle Play Therapy for Alleviating Anxiety in Hospitalized Preschool Children - Prawita Sari, Oktaviany Ayu; Maryatun, Maryatun; Ratrinaningsih, Suciana (Inspirasi Foundation, 2024)
Objective: The aim of this study is to explore the effectiveness of puzzle play therapy in reducing anxiety levels among hospitalized preschool children (aged 3–6 years old) in the Flamboyan Ward at Dr. Moewardi Hospital. Method: Using a descriptive approach, the research adopts a case study design. Results: Both participants demonstrated a reduction in anxiety levels as per the Preschool Anxiety Scale (PAS) assessments conducted before and after the intervention. An. Ab’s anxiety level decreased from 4 (very severe anxiety) to 2 (moderate anxiety), while An. Ak’s anxiety level decreased from 3 (severe anxiety) to 1 (mild anxiety). Conclusion: The findings indicate that puzzle play therapy effectively reduces anxiety levels in preschool children, including those with severe and very severe anxiety levels. The author’s implementation of puzzle play therapy has proven to be successful in alleviating anxiety in children.